Health worker transfer processes within the public health sector in Ghana: a study of three districts in the Eastern Region - A. C. S. Heerdegen; M. Bonenberger; M. Aikins; P. Schandorf; P. Akweongo; K. Wyss (BMC, 2019)
Abstract Introduction The lack of appropriate policies and procedures to ensure transparent transfer practices is an important source of dissatisfaction among health workers in low- and middle-income countries. In order to alter and improve current practices, a more in-depth and context-specific understanding is needed. This study aims to (1) identify rationales behind transfer decisions in Ghana and (2) examine how transfers are managed in practice versus in policies. Methods The study took place in 2014 in three districts in Eastern Ghana. The study population included (1) national, regional, and district health administrators with decision-making authority in terms of transfer decisions and (2) health workers who had transferred between 2011 and 2014. Data was collected through semi-structured and structured face-to-face interviews focusing on rationales behind transfer decisions, health administrators' role in managing transfers, and health workers' experience of transfers. A data triangulation approach was applied to compare identified practices with national policies and procedures. Results A total of 44 health workers and 21 administrators participated in the study. Transfers initiated by health workers were mostly based on family conditions and preferences to move away from rural areas, while transfers initiated by administrators were based on service requirements, productivity, and performance. The management of transfers was not guided by clear and explicit procedures and thus often depended on the discretion of decision-makers. Moreover, health workers frequently reported not being involved in transfer decision-making processes. We found existing staff perceptions of a non-transparent system. Conclusion Our findings suggest a need to foster incentives to attract and retain health workers in rural areas. Moreover, health worker-centered procedures and systems that effectively guide and monitor transfer practices must be developed to ensure that transfers are carried out in a timely, fair, and transparent way.